Wavelet and PCA to Power Quality Disturbance Classification Applying a RBF Network - Pozzebon, Giovani G.; Machado, Ricardo Q.; Gomes, Natanael R.; Canha, Luciane N.; Barin, Alexandre (IntechOpen, 2011)
None